ADAPTATION STUDY OF SOME NEW SUPERIOR VARIETIES OF RICE IN DISTRICT OF SERAM BAGIAN TIMUR - Wahid Wahid; Maryam Nurdin (Widyariset, 2013)
This study was aimed to obtain at least 2–3 varieties which produce high quality and good adaptation in Maluku. The study was conducted in rice fields the village of Jakarta Baru, the Regency Seram Bagian Timur in 2011. The experiment was laid out in a Randomized Block Design with three replications and five treatments. Legowo model 4:1 with plant spacing of (20 cm x 10 cm) x 40 cm was used as a cropping system. The measured parameters consisted of plant height, number of productive tillers per hill, panicle length, number of grains per panicle, total grain weight (g)/hill, and the dry grain yields/hectare (ton/ha). Results showed that among five tested varieties, Inpari 13 has the highest production followed by Conde variety suggesting that both Inpari 13 and Conde varieties are promisingly varieties to be developed in the district of Seram Bagian Timur.